Dialogue on temporary incapacity benefit: the most demanded subject in the Federal Special Courts in the base years 2015 to 2019 (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This article aims to investigate the temporary disability aid/social security sickness benefit as it is the most recurrent subject in the space of the Federal Special Courts from the year 2016 (base year 2015) to the year 2020 (base year 2019), according to statistical indicators, subsequently prepared and published by the National Council of Justice, in the analytical report “Justice in Numbers”. In this regard, the aforementioned benefit in kind is unveiled through the case study of a legal action that refers to this matter, which was filed, by the electronic platform Electronic Judicial Process, in a Federal Court in Maranhão.
Keywords: Federal Special Courts; Most recurring demand; Temporary disability aid; social security sickness benefit